Effects of regional and local atmospheric dynamics on the aerosol and CCN load over Athens. (15th January 2019) - Solomos, S.; Bougiatioti, A.; Soupiona, O.; Papayannis, A.; Mylonaki, M.; Papanikolaou, C.; Argyrouli, A.; Nenes, A.
Abstract: Aerosol and cloud condensate nuclei (CCN) measurements in the area of Athens during HyGRA-CD campaign (May–June 2014) identified a significant diversity in particle properties. In this study we select two distinct cases in terms of meteorology and air mass origin in order to analyze the transport mechanisms inside the Planetary Boundary Layer (PBL) and in the free troposphere and discuss the possible contribution of aerosol in cloud formation. The detection of aerosol layers was based on the lidar technique using multi-wavelength detection schemes. The first case is characterized by a double dust layer arriving over Athens with a shallow and younger plume centered at about 1.8 km and a deeper and more aged plume centered at 3.4 km. These layers originate from different sources and follow different transport paths in the atmosphere which explains also their different optical/geometrical properties. The second case is typical of frontal activity and low cloud formation during daytime. Low level convergence of maritime and continental air masses enhances the updraft velocities inside Athens basin and results in CCN activation and cloud formation along the frontal line. Highlights: Aged and fresh dust coexists with marine and local anthropogenic emissions. First study to examine CCN activation over Athens using detailed modeling and observations. Vertical wind component is the main driving factor for the formation of clouds. Aerosol properties affect CCN activation and cloud condensates size and numbers.